2015
DOI: 10.3390/s151027174
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Strain Measurements on Automotive and Aeronautic Composite Components by Means of Embedded Fiber Bragg Grating Sensors

Abstract: The measurement of the internal deformations occurring in real-life composite components is a very challenging task, especially for those components that are rather difficult to access. Optical fiber sensors can overcome such a problem, since they can be embedded in the composite materials and serve as in situ sensors. In this article, embedded optical fiber Bragg grating (FBG) sensors are used to analyze the vibration characteristics of two real-life composite components. The first component is a carbon fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…After production, the FBG sensor network was used to perform dynamic measurements in order to detect the first eigenfrequencies of the component and compare them with the one obtained from a well-established Laser Doppler Vibrometer modal analysis technique. The results are disclosed in the work of Lamberti et al [ 37 ].…”
Section: Discussionmentioning
confidence: 95%
“…After production, the FBG sensor network was used to perform dynamic measurements in order to detect the first eigenfrequencies of the component and compare them with the one obtained from a well-established Laser Doppler Vibrometer modal analysis technique. The results are disclosed in the work of Lamberti et al [ 37 ].…”
Section: Discussionmentioning
confidence: 95%
“…Copyright 2016, Elsevier. C) Adapted under the terms of CC BY 4.0 Creative Commons Attribution License . Copyright 2015, The Authors.…”
Section: Structural‐health Monitoring With Embedded Sensorsmentioning
confidence: 99%
“…In other examples, sensors were placed at strategically selected places on rotor blades, which allowed bending loads to be monitored (Figure b), or to detect damage . Fiber‐optic Bragg grating sensors were also used in aeronautic and automotive composite components (Figure c) . The sensors were embedded into the composites during resin transfer molding.…”
Section: Structural‐health Monitoring With Embedded Sensorsmentioning
confidence: 99%
“…Recently, Bragg grating fabrication based on various materials or special fiber structure design is emerging rapidly [18][19][20][21], for instance, a chirped Bragg grating on microstructured polymethyl methacrylate fiber proposed by Korganbayev et al (2018) [22] that demonstrated excellent sensitivity for thermal profile detection; and some multicore fibers (MCFs) have been used as fiber optic three-dimensional shape sensors such as the helical MCF with continuous grating developed by Lally et al (2012) [23] for real-time shape sensing using the optical frequency domain reflectometry technique. Such sensors have been widely applied in civil engineering [24], healthcare medical devices [25,26], structural engineering [27,28], aerospace [29], oil and fuels [30], and harsh environments [31], among others.…”
Section: Introductionmentioning
confidence: 99%